Creating communities: the use of technology in craft and DIY communities of practice. Issue 4 (4th November 2014) - Holmes, Kate; Greenhill, Anita; McLean, Rachel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to gain insight into craft and do-it-yourself (DIY) communities of practice (COPs) and how the use of technology provides ways for participants to connect, share and create. Gaining deeper insights into the practices of these communities may provide new opportunities to utilise within this flourishing domain. Design/methodology/approach – Qualitative methods were adopted to collect data and analysed through an interpretivist lens. Semi-structured interviews were conducted with members of craft and DIY COPs to gain a deep understanding of the broader ethnographic study. Existing theoretical perspectives surrounding COPs have been applied to further current perspectives. Findings – Findings from this study suggest that being part of a COP allows participants to connect to others, build creative enterprise and learn or enhance skills. Insights gained from this study indicate some of the detailed ways in which the application of technology redefines craft and DIY COPs. Research limitations/implications – This study provides a succinct exploration of a vast and fluid domain; if presented with more time and wider resources, the research would include further exploration of virtual COPs. Originality/value – The investigation provides a rich insight into the use of information and communication technologies (ICTs) within craft and DIY COPs. The application of theoretical perspectives from the area of Information Systems (IS) and Technology Management to this domain is regarded as an original research and furthers knowledge in these areas. Originality/value – The investigation provides a rich insight into the use of ICTs within craft and DIY COPs. The application of theoretical perspectives from the area of IS to the domain of craft and DIY culture is original research and extends existing concepts to include skills sharing as a previously unexplored domain.